A2_9 Beaming energy - Wilson, Mark; Evill, Ry; Johnson, Christopher; Rolfe, Samantha (Physics Special Topics, 2009)
If a solar shade was placed in space between the Earth and the Sun, it could be converted to gather the solar energy it is designed to block. This paper examines the amount of useful power that such a collector array could yield when beamed to a satellite orbiting the Earth. It is found that using a collector array of area 7.45x1012 m2 and a doped insulator laser, a power of 1.81 W is achievable.